PENGARUH PERENCANAAN PAJAK, UKURAN PERUSAHAAN DAN PENGHINDARAN PAJAK TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SEKTOR BARANG KONSUMSI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021-2024 - Ratna Putri Mardianti; Ita Mustika; Andi Hidayatul Fadlilah (LPPM Universitas Putera Batam, 2026)
This study examines how earnings management is affected by economic pressures and tax strategies in food and beverage companies listed on the Indonesia Stock Exchange from 2021 to 2024. The population in this study consisted of 30 companies, and the sample taken was 17 companies. This sample was determined using a purposive sampling technique, resulting in a total of 68 observations. The purpose of this study was to examine how tax planning, company size, and tax avoidance affect earnings management, both separately and simultaneously. The method used was a quantitative approach using secondary data derived from company annual reports. The data analysis technique used was multiple linear regression. The study shows that tax planning and company size have no significant impact on earnings management. However, tax avoidance has a significant positive effect on earnings management. All variables influence earnings management simultaneously. The conclusion of this study indicates that tax avoidance is a major factor driving earnings management practices and emphasizes the importance of transparency in financial reporting. The implications of this study suggest that companies should improve transparency in their financial statements to reduce earnings management practices, especially those related to tax avoidance. This also needs to be a concern for investors and regulators when making decisions and conducting supervision.